IMPLICATION OF A 12 PERCENT VALUE ADDED TAX INCREASE ON FARMERS’WELFARE IN INDONESIA - Andi Asrijal; Mardi Mardi; Abdul Rahman; Asriadi Asriadi (Adisam Publisher, 2025)
This study is a qualitative study with a descriptive approach, namely an approach that describes the main problem, namely around the twelve percent value added tax increase policy on farmer welfare. The data used in this article is secondary data that researchers obtain from various credible sources such as books, scientific journals, scientific magazines, credible websites, and various other sources that are commonly used in each study. The existing data is analyzed by the stages of data collection, data selection, data reduction, and drawing conclusions with a more comprehensive explanation below.